PENGEMBANGAN SISTEM INFORMASI PEMANTAUAN KINERJA KARYAWAN MENGGUNAKAN FEATURE-DRIVEN DEVELOPMENT - Mohammad Asrofil Nadib; Agus Herwanto; Baddie Uddin; Popong Setiawati (STMIK Catur Sakti Kendari, 2026)
This study examines the implementation of an employee performance management system based on Objectives and Key Results (OKR) at PT Permodalan Nasional Madani (PNM). PNM has been measuring employee performance manually using spreadsheets, which are then printed and evaluated by management. The current business process uses a non-integrated system, making it difficult to monitor employee performance levels in real time and to generate reports. Furthermore, the evaluations tend to lack objectivity because they are not supported by system transparency and still rely on the subjective perceptions of management. This study employs the Agile software development methodology with the Feature-Driven Development model, built using the Laravel framework and MySQL as the database. The results of black-box testing align with the application’s functional and non-functional requirements. The system can perform functions for managing employee data, user data, OKR data, realization data, value calculations, and report generation in the form of tables and graphs. In the performance evaluation process, the Weighted Product algorithm is used for objective assessment. All these processes are integrated to optimize performance and generate accurate, timely, and useful information for subsequent decision-making.